Subcutaneous Tissue Responses to Three Endodontic Irrigants: A Comparative Study - Yazdi, Kazem Ashofteh; Sabeti, Mohammad; Motahhary, Pooriya; Kolahdouzan, Alireza; Shayesteh, Mohsen; Shokouhinejad, Noushin (Iranian Endodontic Journal, 2012)
Introduction: This study aimed to compare the subcutaneous tissue responses to MTAD (mixture of a tetracycline isomer, an acid, and a detergent), 17% EDTA, and 2.6% NaOCl. Materials and Methods: Thirty-six Wistar albino rats were used for this study. Test solutions were injected subcutaneously into predetermined areas on the animal dorsum. The rats were then randomly divided into three groups of twelve each and sacrificed at 2 hours, 2 days, and 2 weeks. The severity of inflammation induced by each irrigant at different time intervals was assessed histologically. The data were analyzed using Kruskal-Wallis and Friedman tests. Results: The difference in severity of inflammatory reactions induced by tested irrigants at the different time intervals was statically significant (P<0.05). There was no significant difference between the severity of inflammation induced by MTAD and 2.6% NaOCl at the various time intervals (P>0.05). Subcutaneous tissue responses to MTAD were not different from those observed in 17% EDTA specimens at 2-hour and 2-day intervals (P>0.05). Conclusion: Under the conditions of this study, MTAD has the same toxicity as 2.6% NaOCl.